Foreign direct investment and onshore employment dynamics: Evidence from German firms with affiliates in the Czech Republic. (15th November 2021) - Koerner, Konstantin; Moritz, Michael; Schäffler, Johannes
Abstract: In this paper, we revisit questions about the onshore employment effects of firms that conduct foreign direct investment (FDI) in countries with substantially lower average wages. Our results derive from the use of rich administrative records on the universe of employees in German multinational enterprises (MNEs) that were active in the Czech Republic in 2010. Compared with former studies, the unique data set in this study includes a much higher fraction of small‐ and medium‐sized firms and leads to strikingly different results for service MNEs. Applying coarsened exact matching for firms and an event‐study design, we show that the domestic employment growth of MNEs decreases relative to that of non‐MNEs and that the affected workers are those with low or medium educational attainment in the manufacturing sector and with medium or high educational attainment in the service sector. Regarding workers' tasks, our results do not show that FDI affects routine jobs beyond a worker's skill level.